Sex, susceptibility to smoking and chronic obstructive pulmonary disease: the effect of different diagnostic criteria. Analysis of the Health Survey for England. Issue 7 (1st March 2012) - Jordan, Rachel E; Miller, Martin R; Lam, Kin-bong Hubert; Cheng, K K; Marsh, Jennifer; Adab, Peymané
Abstract : Background: Some previous studies suggest there are sex differences in susceptibility to, and prevalence of, chronic obstructive pulmonary disease (COPD) but findings are inconsistent. In this study, whether different diagnostic criteria for COPD may contribute to these conflicting findings was examined. Methods: Cross sectional analysis of data from the 1995, 1996 and 2001 Health Survey for England was undertaken, including participants of white ethnicity, aged 40+ years with a valid smoking history and lung function data. COPD was defined using Global Initiative for Chronic Obstructive Lung Disease (GOLD), National Institute for Health and Clinical Excellence (NICE) and lower limit of normal (LLN) spirometric criteria, in the absence of a diagnosis of asthma. Results: COPD was present in 3035 (16.1%), 1304 (7.0%) and 1684 (9.0%) people, according to the GOLD, NICE and LLN criteria, respectively. With both the GOLD and NICE definitions, men had significant independent increased risks of COPD compared with women (OR 1.46 (95% CI 1.34 to 1.59) and 1.30 (1.15 to 1.48), respectively). With the LLN definition, this effect was removed (OR 0.96 (0.87 to 1.07). With the use of both the GOLD and NICE criteria, women had significantly greater susceptibility to COPD (25–30% higher risk) for the same level of pack years of exposure. This was not observed with the LLN criteria. Conclusions: The study indicates that sex differences in risk of COPD reported in previous studies are influenced by the definition used for COPD. When using a statistically driven definition (LLN), no independent sex difference was found and there was no evidence of an increased susceptibility to COPD among female compared with male smokers.